Knowledge Infrastructures Require Scaffolding: The role of personal relationships in information management - Schmidt, Gisela (Septentrio Conference Series, 2023)
Watch VIDEO. Knowledge infrastructures are multi-faceted, ever-shifting networks of people and information. They span departments, address varying needs and, ideally, provide stability despite personnel turnover and other changes. Information is made explicit and available via organizational charts, procedural manuals and regular meetings, ensuring members of an institution are kept up-to-date with necessary information. Moving below and between these formal channels, however, is the informal network, a web of unquantifiable, personal relationships, which are nevertheless vital to the functioning of the system. Developing and maintaining a system that works for the current and future needs of diverse groups—e.g., a publication repository used by administrative and research staff—involves tapping into the existing knowledge infrastructure at multiple points, in both the formal departments and the spaces between them. In addition to the stakeholder meetings and the lists of user requirements, we have the informal conversations where we can learn the tacit information, for example, how research groups are defined by different parties and whether software versions are considered separate publications. It takes time to learn the right questions and to learn who might hold the answers or, if there is no pre-existing solution, with whom you can work to establish one. In this session, we will use the example of a publication repository to discuss the role of personal relationships throughout a project lifecycle, from conception through rollout and ongoing updates. I invite you to consider how to support the development of the informal network, how to identify tacit knowledge and information gaps, and how to take personality and communication skills into account when hiring for technical positions.